Avaliação do estado nutricional de pacientes portadores de cirrose hepática em atendimento ambulatorial: parâmetros clínicos, antropométricos, bioquímico e hematológico - Vieira, Patrícia Maria (2005)
OBJECTIVE - To assess the frequency of malnutrition in ambulatory patients with hepatic cirrhosis (HC). METHODS - Seventy-eight patients were evaluated, 56.4% were male and 43.6% were female, mean age (standard deviation) 53.0 ± 7.7 years. The HC etiology was alcoholic in 56.4% of the cases, hepatitis C virus in 17.9%, hepatitis B virus in 15.4%, autoimmune in 2.6% and cryptogenic in 7.7%. According to the classification of Child-Pugh, 48.7% were A, 26.9% were B and 24.3% were C. Their nutritional state was determined by a subjective global assessment (SGA); body mass index (BMI); percentage of adequation of body weight (%BW), of triceps skinfold thickness (%TST), of mid-arm circumference (%MAC) and of the mid-arm muscle circumference (MAMC); serum albumin (ALB) and total lymphocyte count (TLC). RESULTS - Variable degrees of malnutrition were diagnosed in 61.5% (SGA), 16.7% (BMI), 17.9% (%BW), 93.5% (%TST), 62.8% (%BC), and 38.5% (MAMC) of the patients. The levels of ALB and TLC were compatible with malnutrition diagnoses in 43.5% and 69.3% of the patients, respectively. The frequency of diagnoses of malnutrition increased according to the severity of HC and it also increased in patients with alcoholic etiology. A greater depletion of adipose tissue in women and of muscular tissue in men was demonstrated. CONCLUSIONS - Malnutrition is frequent in ambulatory-treated patients. However, its diagnostic frequency varies according to the nutritional evaluation method used. The prevalence of malnutrition is greater in the more advanced stages of HC and in alcoholic etiology.